Cyclic oxidation and rumpling behaviour of single phase β-(Ni, Pt)Al coatings with different thickness of initial Pt plating. (October 2016) - Yang, Y.F.; Jiang, C.Y.; Yao, H.R.; Bao, Z.B.; Zhu, S.L.; Wang, F.H.
Graphical abstract: A dual-layered alumina scale consisting of upper equiaxed and inner columnar grains was observed on the β-(Ni, Pt)Al coating specimen with 5 μm Pt after cyclic oxidation at 1100 °C for 200 cycles. The corresponding SAED patterns (b and c) confirm hexagonal crystal structures for the equiaxed and columnar α-Al2 O3 grains, respectively. This unique structure of dual-layer was beneficial for the decreased oxidation rate, and the precipitation of Pt-rich particles along columnar alumina grain boundary may assist to block the outward transportation of Al cations. Highlights: ⿢ Dual-layered α-Al2 O3 scale was formed on (Ni, Pt)Al coating after oxidation. ⿢ Pt-rich precipitates were observed in columnar grains of Al2 O3 scale. ⿢ Higher Pt content in (Ni, Pt)Al coating results in lower Young⿿s modulus and hardness. ⿢ Besides phase transformation, coating deformability was important to affect rumpling. ⿢ Al depletion rate was accelerated in turn by severer morphology rumpling. Abstract: Cyclic oxidation behaviour of single phase β-(Ni, Pt)Al coatings with different thickness of initial Pt plating was evaluated at 1100 °C in air. The coating sample of 5 μm Pt showed the best oxidation resistance, and after oxidation a dual-layered structure of alumina scale was formed on this coating with precipitation of Pt-rich particles at both boundary and interior of columnar α-Al2 O3 grains. Comparatively, the coating sample with 8 μm Pt was prone to rumpling due to its lower hardness and Young⿿s modulus, while the severer rumpling behaviour in turn increased the scale spallation tendency and Al depletion rate.